Factors associated with critical care needs in patients presenting with ST-elevation myocardial infarction: impact of early decompensation and culprit lesions - Jnani, Jack; Weintraub, Spencer F.; Sood, Aditya; Cheng, Austin; Kamel, Maikel; George, Riya; Impastato, Brandon; Srivastava, Shreya; Hsieh, Ji-Cheng; Wallach, Yisrael; Lin, Allan; Tsai, Andrew; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPatients with ST-elevation myocardial infarction (STEMI) are often admitted to the cardiac intensive care unit (CICU), though not all require advanced therapies. Identifying predictors of critical care need may improve triage and resource allocation.MethodsWe performed a retrospective cohort study of 758 patients admitted with STEMI to a quaternary care CICU from 2018–2022. The primary outcome was critical care need, which was defined as use of mechanical ventilation, titratable infusions (vasoactive, sedative, or anti-arrhythmic), or mechanical circulatory support. Multivariable logistic regression was used to identify predictors of critical care need.Results141 out of 758 patients (18.6%) utilized critical care resources, with the majority initiated before CICU admission (71%). We found that a history of chronic kidney disease (OR 4.3, 0.96–17.5, p = 0.05), STEMI in the post-COVID era (OR 2.7, 95% CI 1.45–5.09, p = 0.002), a Modified Shock Index on admission ≥ 0.93 (OR 4.04, 2.04–8.08, p < 0.001), and a lower ejection fraction (OR 0.97, 0.94–0.99, p = 0.007) were independent predictors of having critical care needs. Presence of a severe coronary stenosis (>70%), which was typically revascularized, did not increase critical care need, whereas multivessel coronary disease significantly did (OR 3.06, 1.64–5.83, p < 0.001).ConclusionThe majority of patients in our cohort did not require critical care resources after a STEMI, and a majority of those that did developed those needs prior to admission. A history of chronic kidney disease, elevated Modified Shock Index, reduced ejection fraction, and multivessel disease were associated with critical care needs while culprit vessel involvement was not.